Hubungan Pendidikan Ibu Dan Paritas Dengan Perkembangan Anak Balita Umur 3-4 Tahun Di PAUD Baitul Izzah Kota Bengkulu - Arum Kusuma Rini (Poltekkes Kemenkes Surakarta, 2017)
Abstract: Mothers Educations, Parity, Early Children Under Five Development. This research aimed to know the relationship of mother and parity education with early children under five development in PAUD Baitul Izzah Bengkulu City. The studied used analytic survey research design. With Cross-Sectional research methods. The population in this studied were all children under five in PAUD Baitul Izzah Bengkulu City that is 28 infants age 3-4 years. Sampling technique in this studied used the Total Sampling means all children under five years, amounted to 28 children. The result obtained from maternal education and party relationship with the development of children under five age 3-4 years in PAUD Baitul Izzah Bengkulu that of 28 of children under five there were 10 (35%) of people who did not good children under five development or 18 good children under five development, Than 28(100%) of children there were 3 (10,7%) of the mothers, children under five and secondary education (89,3%) of the mothers infants of higher education. And there were 17 infants with parity multiparous mother, and 11(39.9%) of the mother, children under five parity primipara.